2023
DOI: 10.1140/epjc/s10052-023-11369-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Lorentz symmetry breaking effects on GRBs jets arising from neutrino pair annihilation process near a black hole

Abstract: The study of neutrino pair annihilation into electron-positron pairs ($$\nu {\bar{\nu }}\rightarrow e^-e^+$$ ν ν ¯ → e - e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…He found when the BH is surrounded by a plasma region with a weak magnetization, the energy extraction due to magnetic reconnection increases for negative values of LSB parameter. Khodadi et al [21] explored the rate of energy deposition for gamma-rays induced by the annihilation of neutrino pairs for a slowly rotating BH, with modifications due to spontaneous LSB, specifically considering the plane passing through the equator. It was found that the energy deposition rate is increased for positive values of LSB parameter.…”
Section: Jcap05(2024)047mentioning
confidence: 99%
“…He found when the BH is surrounded by a plasma region with a weak magnetization, the energy extraction due to magnetic reconnection increases for negative values of LSB parameter. Khodadi et al [21] explored the rate of energy deposition for gamma-rays induced by the annihilation of neutrino pairs for a slowly rotating BH, with modifications due to spontaneous LSB, specifically considering the plane passing through the equator. It was found that the energy deposition rate is increased for positive values of LSB parameter.…”
Section: Jcap05(2024)047mentioning
confidence: 99%
“…in the region where the DM density is high), using the so-called Bumblebee Gravity model. This model extends the standard framework of GR and allows for spontaneous Lorentz symmetry breaking through a non-zero vacuum expectation value of the bumblebee vector field B µ under a suitable potential [60,61]. The bumblebee model is an example of a theory that exhibits Lorentz violation arising from a single vector B µ that acquires a non-zero vacuum expectation value, and it is among the simplest field theories with spontaneous Lorentz and diffeomorphism violations [62][63][64][65][66][67].…”
Section: Jcap05(2023)027mentioning
confidence: 99%
“…These different frameworks have been used to analyze a wide range of experimental tests of spacetime symmetry in gravity theories [25]. In addition, specific models exhibiting spontaneous spacetime symmetry have been constructed and investigated [15,16,29,30], including Bumblebee models, where numerous applications have been explored (for examples, see [122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137]).…”
Section: Spontaneous Breakingmentioning
confidence: 99%